Perilaku Penjamah Makanan Jajanan Dan Tingkat Kontaminasi Mikroba Di Kantin Sekolah - Budi Lestari, Asriyah; Haniarti, Haniarti; Umar, Fitriani; Sudarman, Dirman (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2024)
Food handlers play an important role in ensuring food quality and safety. Their lack of awareness of healthy behavior, personal hygiene, equipment, and food sanitation are the main causes of food contamination. This study aims to determine the level of microbial contamination in canteen snacks and the behavior of food handlers at SMA Negeri 2 Barru, in order to show that the food processed does not contain bacteria due to the behavior of food handlers. The research method used quantitative analytics with a descriptive approach. Respondents consisted of 10 food handlers in the school canteen. For the examination of food samples such as tofu stuffed meatballs, stuffed tofu, bakwan, carrot bakwan, wonton skin, somay and Salmonella content identification was carried out at the Makassar Public Health Center (BBLK). The results showed that 70% of the handlers did not know the importance of sanitary hygiene principles, 40% did not know the correct action if they found insects in the kitchen, and 70% did not know the importance of not using accessories when touching food. The results of the examination of food samples showed that the food served by the canteen food handlers met the requirements because it was negative for Sallmonela bacteria. This study found several things that did not meet the requirements of hygiene and sanitation principles, some of which included food handlers not knowing the correct action if they found insects in the kitchen, the importance of not using accessories when touching food, and how to store raw and cooked food separately in the refrigerator. It is also necessary to ensure cutlery and drinking utensils are clean before use and understand the different roles in payment acceptance. It is expected that school canteen owners pay more attention to the process of washing cutlery, change cloths regularly, store cutlery in a closed and non-moisturized place, and provide enough water to clean cutlery. Keywords: Handler knowledge, Behavior, Salmonella.